On linearly related sequences of derivatives of orthogonal polynomials - Jesus, Márcio (2014)
We discuss an inverse problem in the theory of (standard) orthogonal polynomials involving two orthogonal polynomial families n(Pn) and n(Qn) whose derivatives of higher orders m and k (resp.) are connected by a linear algebraic structure relation such as (...)